Emilu rozwijaj się, albo… Poza edukacyjną dyscyplinę - Maksymilian Chutorański (Problemy Wczesnej Edukacji)
In my paper I will argue that the development and the need of support of development (also in Rousseau sense) takes a strategic position in the contemporary power relations. The pedagogical thinking built on the need/demand of support of development can justify the mechanisms of power in a legal scheme, and consequently, to justify them in terms of natural human right. My paper assumes the following order: Firstly, pay attention to the specifics of contemporary power relations. Secondly, problematize the need of support the development and show how educational dispositif works. Thirdly, I ask about the emancipatory potential of Rousseau’s pedagogical ideas.